The Quasi-Biweekly Oscillation of Summer Rainfall in Southern China and Its Relationship With the Geopotential Height Anomaly Over the North Atlantic Ocean - Huang, Qian; Yin, Xinyu; Yao, Suxiang (Frontiers in Earth Science, 2021)
Summer precipitation in East Asia has significant quasi-biweekly (10–30-day) oscillation characteristics. By using gauge-based precipitation and ERA-Interim reanalysis data, the basic mode of the quasi-biweekly oscillation of summer precipitation in East Asia and the related circulation from 1979 to 2012 were analyzed. It was found that the middle and lower reaches of the Yangtze River and its south in China were among the key areas for the 10- to 30-day oscillation of summer precipitation. After selecting typical summer precipitation events with 10- to 30-day oscillation characteristics in key areas and conducting composite analysis, it is found that in the dry (wet) phase of quasi-biweekly precipitation in southern China, it is controlled by quasi-biweekly anticyclone (cyclone) at 500 hPa above the key area. During the evolution of quasi-biweekly precipitation, the ridge of the Northwest Pacific Subtropical High is located between 20 and 22°N latitude, and there is no significant variability in the large-scale background circulation. Furthermore, composite analysis of the precursory signal at 500 hPa during quasi-biweekly precipitation in southern China found that there was an obvious quasi-biweekly geopotential height anomaly over the North Atlantic Ocean almost 30 days before the peak day of quasi-biweekly precipitation. While the quasi-biweekly geopotential height anomaly at 500 hPa in the North Atlantic propagates eastward, it also leads the cold air to transport southward. Cold air from high latitudes and warm air from low latitudes converge in southern China, which affects the quasi-biweekly oscillation of precipitation. Hysteresis synthesis of precipitation based on 500 hPa geopotential height’s quasi-biweekly oscillation events over the North Atlantic Ocean comes to almost the same conclusion. Therefore, the 500 hPa geopotential height quasi-biweekly anomaly in the North Atlantic may have important prediction significance for an extended-range forecast of summer rainfall in China.